LANE CHANGING CHARACTERISTICS FOR DIFFERENT TYPES OF ROADS IN NAJAF - AL-JAMEEL, HAMID A.; KADHAM, ALI JIHAD (Journal of Duhok University, 2021)
Investigating a driver behavior under different traffic conditions is the main point to develop a microscopic traffic model such as the Frequency of Lane Changing (FLC) and Lane Utilization (LU). The LC model is the corner stone for developing each traffic software; especially traffic simulation models. The main aim of this study is to investigate the FLC and LU under different traffic conditions such as urban and rural roads. Furthermore, the FLC for each type of road two-or three-lane sections has been investigated. Field data have mainly been collected from urban arterial roads; whereas other published data have been used for this study. High FLC has been observed in Iraqi roads comparing with other countries. This behavior could be attributed to the aggressive behavior and the absence of pavement parking.